EFFECT OF ACIDIC, BASIC AND NEUTRAL SOAPS ON MICROLEAKAGE OF DENTIN BONDING AGENT - H Safarcherati (Babol University of Medical Sciences, 2008)
BACKGROUND AND OBJECTIVE: Microleakage of composite restorations causes postoperative sensitivity, marginal staining and recurrent caries. The aim of this study was to reduce microleakage of tooth-colored restorative materials by preparing dentin surface for dentin bonding agents with acidic, basic and neutral soaps as a wetting agent.METHODS: This study was performed on box only cavities in 60 extracted human premolars for detecting microleakage by dye penetration. Based on acidic, basic, neutral and control soaps, the teeth were randomly divided into four groups. In groups 1, 2 and 3 after acid etching and washing, acidic (pH=4.5), basic (pH=9.5) and neutral (pH=7) liquid soaps were applied on dentinal surfaces for 30 seconds and washed for 30 seconds, respectively. Group 4 was considered as a control group without using soaps. After washing, excite dentin bonding agent and tetric ceram composite resin were used in the cavities according to the manufacturer recommendations in all groups. FINDINGS: The mean rank of microleakage grades in groups 1 (acidic soap), 2 (basic soap), 3 (neutral Soap) and 4 (control) were 27.4, 37.7, 21.9 and 35.1, respectively. There was a statistically significant relationship among groups and neutral soap group had lower microleakage grade in comparison with basic and control groups. (p=0.013 and p=0.045).CONCLUSION: Application of dentin bonding agents with neutral soap showed promising results in reducing microleakage.